Patent Ductus Arteriosus Stenting via Percutaneous Common Carotid Artery Access for Ductus Dependent Pulmonary Blood Flow in Newborns and Infants: Experience in Latvia - Grīnberga, Zanda; Zaharāne, Elizabete; Sīlis, Pauls; Ozoliņš, Valts; Sikora, Normunds; Ligere, Elīna (Acta medica Lituanica, 2024)
Background: Newborn patients with cyanotic congenital heart diseases with ductus-dependent pulmonary blood flow require neonatal repair, or palliation with a secure source of pulmonary blood flow, up to definitive surgical correction or palliation of the malformation. There is growing experience of percutaneous patent ductus arteriosus stenting to maintain the ductal flow. Patients in need of PDA stenting are newborns or small infants and recent data suggests that a weight of
Keywords: PDA stenting; percutaneous transcarotidal approach; duct-dependent pulmonary circulation; cardiac catheterization; pediatric cardiology